Development and evaluation of the Digit Triplet Test in Swahili language - Bjørn G. Rosendahl; Tron V. Tronstad; Jon Øygarden (South African Journal of Communication Disorders)
Background: The development of a Digit Triplet Test in the Swahili language is an essential step towards providing accurate hearing assessment for Swahili-speaking populations.